Comparanda: Il Papiro di Artemidoro e i suoi apparati graﬁci - Settis, Salvatore (Hyperboreus, 2019)
A proper archaeological comparison, while based on immediate and convincing visual aﬃnities, must also be veriﬁed and controlled according to parameters of a properly historical, and art historical, nature. The “Papyrus of Artemidorus”, with its three series of drawings (a map, numerous animal drawings and a series of ﬁgure drawings) lends itself to considerations of great methodological interest. Some comparisons that have been proposed do not stand up to the test of historical analysis, but the search for other comparisons (or comparanda) opens new avenues for research, which this paper explores in part. The central role of drawing in ancient art, so diﬃcult to grasp from an extremely fragmented documentation, can at least in part be understood by widening the gaze from the few drawings on preserved papyrus (about 1000 are known) to other monumental classes: coins, graﬃti, paintings, vases, sculptures.